ANALISIS YURIDIS PEMBATALAN PERKAWINAN KARENA PERGANTIAN AGAMA DAN AKIBAT HUKUMNYA DITINJAU DARI HUKUM ISLAM - JUMIATI HARAHAP (PREMISE LAW JURNAL, 2016)
One of the interesting things in Marriage law is about marriage cancellation. Based on Article 22 of Marriage Law, it is said that if a marriage does not meet marriage requirements, it can be cancelled. It is possible for a marriage, which is religiously valid but does not follow the rules and laws, according to Article 22 of Marriage Law, to be cancelled.The research used descriptive analytic and judicial normative method. The conclusions of the research were as follows: Islam highly emphasizes on the requirement for the same religion in wedlock because the purpose of marriage in Islam is a marriage is not solely related to muamalah (relationship among human beings), the judge’s consideration at the Medan Religious Court in his Verdict No 569/Pdt.G/2008/PA.Mdn states that marriage cancellation due to a divorce is not a cancellation and legal consequence of marriage cancellation on the relationship between husband and wife is considered void, the child’s right is not retroactive, and property for the husband and wife who have good faith, except joint property. It is recommended that a marriage couple participate in pre-marriage counseling and judges prioritize the Islamic personality principle. They should be cautious and their consideration be related to the causality of religious conversion in marriage. Keywords: Cancellation, Marriage, Religious Conversion (Apostasy), Legal Consequence